The Apostles' Creed : Born of the Virgin Mary - Sarot, Marcel (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
What does it mean when Christians confess that Jesus was 'born of the Virgin Mary'? This volume of essays, written by an international group of scholars, approaches this question from various perspectives. From examining the Old Testament backgr